Intestinal permeability in children with food allergy on specific elimination diets. Issue 6 (2nd August 2013) - Järvinen, Kirsi M.; Konstantinou, George N.; Pilapil, Mariecel; Arrieta, Marie‐Claire; Noone, Sally; Sampson, Hugh A.; Meddings, Jon; Nowak‐Węgrzyn, Anna
Abstract: Background: Children with food allergy have been shown to have increased small intestinal permeability (IP) following ingestion of the offending food as well as during elimination diets. We investigated IP in asymptomatic food allergic children during an elimination diet to identify clinical characteristics associated with altered IP. Methods: Urinary recovery ratios of lactulose and mannitol (L/M) were determined 5 h following ingestion of 7.5 g of lactulose and 2 g of mannitol in 131 cow's milk and egg allergic children. An L/M ratio of ≥0.025 was considered abnormal based upon previously established laboratory internal references. A chart review was conducted to assess the clinical characteristics of these patients. Results: A total of 50 (38%) of the 131 children (median 6.7, range 4.8–8.9 yr; 66.2% male) with food allergy had elevated IP while asymptomatic on strict elimination diets. Age and height negatively correlated with IP. However, in the regression model analysis, abnormal IP was associated with shorter stature independently of age. Otherwise, food allergic patients with increased IP were comparable in gender, nutritional status, age of onset of food allergy, history of reactions, atopic diseases, and family history of food allergies to those with normal IP. Conclusions: Elevated IP was found in about one‐third of asymptomatic food allergic children on elimination diets and was associated with shorter stature. Our results suggest that increased IP may be an intrinsic trait in a subset of food allergic children. However, large, prospective studies are necessary to determine the role of impaired intestinal barrier in food allergy. Abstract :